Privilegiesamfunnets undergang. En nordisk sammenligning 1750-1880 - Sandvik, Pål Thonstad (Historisk Tidsskrift, 2022)
The Decline of the Old Economic Order: A Nordic Comparison 1750–1880 In 1750, economic freedom in the Nordic countries was restricted through numerous privileges and regulations pertaining to labor, farmland, natural resources, commerce, crafts and financial markets. With economic opportunities to a large extent determined by family background or political status, the Nordic countries were what Douglass North, John Wallis and Barry Weingast characterized as "limited access societies", or, as Daron Acemoğlu and James A. Robinson phrased it, "extractive societies". By 1880, the Nordic economies had been transformed into "open access societies" or "inclusive societies", according to the same set of scholars. The four countries had developed market-based economies where all male citizens shared the same economic rights. Economic privileges, guilds and corvée labour had been all but abolished. With few exceptions, all types of commodities, services and property could be freely exchanged at market prices. Comprehensive economic reforms started in Denmark-Norway in the second half of the 18th century, but were discontinued after c. 1800. In contrast to the French-occupied parts of Europe, the political economy of the Nordic countries was not much altered during the wartime upheavals. After gaining independence (home rule) in 1814, economic reforms resumed in Norway, while Sweden (with Finland until 1809) developed somewhat differently. Only limited reforms were enacted around 1800 and the basic elements of Swedish political economy survived until the death of King Charles John in 1844. Far-reaching reforms were subsequently passed in 1846 and 1864. In post-Napoleonic Denmark and Finland, the political economy was left more or less unchanged until the 1850s; thereafter, reforms were carried out more quickly and radically than in the neighbouring countries. Danish guild privileges were abolished with one stroke in 1857. In comparison, more than 40 years passed between Norway’s initial restrictions on guild and trade rights in 1839 till they were wholly eliminated. The same process took 20 years in Sweden. These differences were hardly coincidental. In the more democratic and egalitarian Norway, the defense of the old order was weaker but reforms were time-consuming, as broad compromises had to be negotiated. In Sweden and especially Denmark and Finland, economic reforms were more likely to stem from royal succession, rulers’ personal preferences, and political upheavals. Hence, reforms were enacted later, but when they were finally introduced, they were swifter and more radical.